Celestine : [large type] a novel - St. Jarre, Kevin (Center Point Large Print, 2022)
"Celestine Tolland returns to a small Maine hometown that she scarcely recognizes. While dealing with personal loss, profound loneliness, and even questioning her sanity, she is plagued by the paranoia of many of the townspeople, who see her as dangerous, and menaced by mysterious government forces who are monitoring her, both overtly and from the shadows. At its heart, this psychological thriller centers around the humanity of a young woman unsure of where to turn and whom to trust."--